Poesia, subjetividade lírica, monodia e mímesis - Calaça, Camila de Souza (2019)
This thesis, starting from the conception that lyric is mimetic due to monody, analyses and describes the modern and contemporary brazilian poetry, taking by corpus a variety os poems and poets from 20th and 21th centuries. Monody is a term, used by us, that refers of the Bakhtinian concept about monology and implies the notion of lyrical subjectivity. Thus, we admit, in the manner of Bakhtin, lyric is monological and we chose using monody, comparing to others literary genres of Modernity, because lyrical monologism is specific, peculiar. In a relation between lyric, monody and mimesis, mediated by Bakhtin’s thoughts, we used key-words as axiological positioning and authorship. Furthermore, considering fundamental to lyric’s studies to understand the relations (of proximity or difference/indifference) among empirical subject and lyrical subject, we used the Margarete Susman, Lukács, Adorno, Combe, Collot and others’ ideas. Concerning lyric as a mimetic genre, Merquior, Achcar e Costa Lima are the names that we used, agreeing or disagreeing with them.